Evaluation and Durability of a Curriculum-Based Intervention for Promoting Mental Health among Graduate Students. Issue 6 (1st November 2020) - Brett, Chelsea; Wang, Katie; Lowe, Sarah R.; White, Marney A.
ABSTRACT: Background: Graduate school environments are recognized for contributing to elevated stress levels among student populations. Purpose : The objective was to test whether a behavioral intervention, delivered through an online course on behavior change, is effective in preventing declining mental health. Methods : Data were collected via a quasi-experimental longitudinal study to observe the effect of self-directed behavioral interventions on mental health. Participants included students enrolled in a course on Health Behavior Change at the Yale School of Public Health (n = 45) and a control group (n = 33) of students in the same graduate program. Analyses were conducted to evaluate differences at post-intervention and at a 12-week follow-up assessment in indicators of mental and general health. Results : Enrolled students reported significantly improved mental health outcomes as compared to the control students. At follow-up, multiple differences persisted, with participants who had completed the course reporting sustained improvements in general and mental health. Discussion : Self-directed behavior change interventions are effective in promoting mental and physical health among graduate student populations. Translation to Health Education Practice : This curriculum-based intervention can support student wellbeing in a variety of academic programs. Abstract :